Management of Sustainable Development as a Task for Coordinated Optimum - Krachunov, Hristo At; Ovcharova, Snezhanka (International Conference on High Technology for Sustainable Development (Online), 2022)
The article presents the initial principles, concepts and definitions for the formulation of the general task for optimal management of sustainable development. The general target function for satisfaction and inherent material and emotional costs of the subjects carrying out exchanges with each other and having a goal for sustainable development is derived. The common task for sustainable development in optimizing the exchange between two or more entities has been formulated. An aggregated algorithm for coherent optimal management to achieve sustainable development of industrial zones and production systems is presented. Conclusions have been made.